Sosialisasi Central Bank Digital Currency (CBDC) Dalam Perspektif Ekonomi Syariah - Swadia Gandhi Mahardika; Akbar Lufi Zulfikar; Rinna Ramadhan Ain Fitriah; Nurfiza Widayati (AMMA : Jurnal Pengabdian Masyarakat, 2024)
From a Sharia Economic Perspective, Central Bank Digital Currency is a type of Fintech. The purpose of this socialization is to learn about it. The aim of this community is to study how Sharia places Central Bank Digital Currency as a currency or medium of exchange, and its influence. They will also see whether it is suitable to be used as a medium of exchange. Furthermore, the functions of money such as medium of exchange, standard of deferred payment, store of value, and unit account are adjusted to the value obtained from CBDC tracking and fiqh analysis. This study will investigate the concept of money and its components, as well as whether CBDCs are fair. Apart from that, this community will provide an explanation of Islamic views, especially Sharia views, regarding CBDC as a currency and medium of exchange.